The influence of sowing season on corn yield under the conditions of current climate changes - Alina Şimon; Voichița Haş; Andrei Varga; Florin Russu; Adrian Ceclan; Felicia Cheţan; Marius Bărdaş (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The purpose of this work is to evaluate the corn production obtained following the change of the sowing date. In the current context of current climate changes, adaptation of cultivation technology is essential to obtain satisfactory quantitative and qualitative results. The experimental factors analyzed in this study are sowing season with three gradations (Season I - 6C in soil; Season II - 8C in soil; Season III - 10C in soil); corn hybrids (Turda 248 - control; Turda 165; Turda 201; Turda Star; Turda 332; Turda 344; Turda 335) and the climatic conditions of the two experimental years (2020; 2021). In 2021, production was lower than in 2020, with 922 kg/ha, the climatic conditions during the vegetation period being the decisive factor in the realization of these productions. All analyzed hybrids recorded a higher average yield when sown at 8C (10504 kg/ha), compared to the other two sowing seasons. Among the analyzed hybrids, the Turda 335 hybrid achieved the highest production (10862 kg/ha), 48 kg/ha more than the Turda 248 control.
Keywords: Q01; Q15; Q16; 330; sowing season; corn; yield; climatic conditions